Греймасын үйлдэгч хэмээх ойлголт ба нэгэн монгол өгүүллэг - Г., Ууганбаяр (Acta Mongolica, 2018)
In this paper, the author discussed the notion of actant and actor which are very popular in literary semiotics structuralism and narrative theory. There are six key actantial roles of functions arranged in three sorts of binary opposition: subject/object; sender/receiver; helper/ opponent. Together the six actants and their organization account for all possible relationships within a story and indeed within the sphere of human action in general. The actantial narrative schema is a simplification of Propp`s seven spheres of action or roles elaborated from a study of the Russian folk tale roles such as those of hero, villain, helper etc. The subject is what wants or does not want to be joined to an object. The sender is what instigates the action, while the receiver is what benefits from it. The helper helps to accomplish the action, while the opponent hinders it. Semiotics uses the term actor to refer to any individual, anthropomorphic or zoomorphic agent, to a group or to an abstract entity such as fate. In semiotic analysis actor has replaced the traditional terms of character or protagonist. Actors individualized and represent concrete figurative elements. On the example of the modern Mongolian love story, Hulan and I by Sengiin Erdene can be thought that the characters Tsamba and Sampil as actors become subject and receiver and Hulan as an actor becomes object and sender.